PENINGKATAN PENGETAHUAN PENULISAN BUKU AJAR PADA GURU-GURU SMP - Jonner Nainggolan; Virman Virman (JURNAL PENGABDIAN PAPUA, 2023)
The teacher is the dominant factor in the learning process at school. In the learning process, teachers are required to master the material being taught. Mastery of the material to be taught is an absolute requirement for the teacher, teachers can make textbooks or modules from the subjects being taught to better understand the material taught by a teacher. Making textbooks requires willingness, perseverance, commitment and lots of references. The sample of this research is the teachers of SMP Negeri 4 Jayapura as many as 17 teachers. The research activity was carried out, first the author gave a pre-test instrument to the teachers about the knowledge of textbook writing. Researchers provide material about the knowledge of writing textbooks, how to collect references, via the internet, textbooks, modules and journals. Textbook writing, code of ethics norms for editing teaching materials, Indonesian grammar according to textbook writing standards. The teaching materials were delivered, followed by questions and answers and discussions with activity participants. The activities carried out went well, it could be seen from the enthusiasm and motivation of the participants to take part in the activities. The materials prepared by the activity implementers were 98% complete. Participants in the activity were 17 participants, from the expected 15-20 teachers. After the material is taught, the post-test instrument is the same as the pre-test. Based on the results of the pre-test and post-test, the teacher gained an increase in knowledge about writing teaching materials with an average n-Gain of 0.41 including the medium category.Keywords: teaching materials; teachers; n-Gain